Case Report: do heart transplant candidates benefit from mechanically supported revascularization? - Pyka, Lukasz; Szkodzinski, Janusz; Piegza, Jacek; Swietlińska, Malgorzata; Gąsior, Mariusz (Frontiers in Cardiovascular Medicine, 2023)
Introduction Recently published studies suggest that PCI has no significant impact on outcomes in patients with heart failure and stable coronary artery disease. The use of percutaneous mechanical circulatory support is growing, but its value is still uncertain. If large areas of viable myocardium are ischemic, benefit from revascularization should be evident. In such instances we should strive for complete revascularization. The use of MCS in such cases is vital, as it provides hemodynamic stability throughout the complex procedure. Case report We present a case of a 53-year-old male heart transplant candidate with type 1 diabetes mellitus, initially considered unsuitable for revascularization and qualified for heart transplantation, transferred to our center due to acute decompensated heart failure. At this time the patient had temporary contraindications for heart transplantation. As the patients was considered no-option, we have decided to reassess the possibility of revascularization. The heart team opted for a high-risk mechanically supported percutaneous coronary intervention (PCI) with the aim of complete revascularization. A complex multivessel PCI was performed with optimal effect. The patient was weaned off dobutamine on the second day post-PCI. Four months post discharge he remains stable, NYHA II, no chest pain. The control echocardiography showed improved ejection fraction. The patient is not a heart transplant candidate anymore. Conclusions This case report shows that in select heart failure cases we must strive for revascularization. The outcome of this patient suggests that heart transplant candidates with potentially viable myocardium should be considered for revascularization, especially as shortage of donors persists. In the most complex coronary anatomy and severe heart failure the use of mechanical support in the procedure might be essential.